Identification of Suitable Areas for West Nile Virus Circulation in Tunisia. Issue 2 (29th May 2015) - Ben Hassine, T.; Conte, A.; Calistri, P.; Candeloro, L.; Ippoliti, C.; De Massis, F.; Danzetta, M. L.; Bejaoui, M.; Hammami, S.
Summary: West Nile virus (WNV) is a mosquito‐transmitted Flavivirus belonging to the Japanese encephalitis antigenic complex of the Flaviviridae family. It is transmitted primarily by the bite of infected mosquitoes, particularly Culex spp. and Aedes/Ochlerotatus spp., which acquire the virus by feeding on viraemic birds. Humans, horses and other mammals are regarded as incidental or dead‐end hosts. In the last decades, an increasing number of cases of WNV infection in horses and humans have been notified in the Mediterranean basin. In Tunisia, human cases of WNV‐related meningoencephalitis were detected in 1997, 2003, 2007, 2010, 2011 and 2012. Based on the analysis of climatic and environmental conditions found in the locations where human cases have been reported in 2012, the aim of this study was to identify similar areas in Tunisia potentially at risk of disease occurrence. Data related to 85 neuroinvasive West Nile fever (WNF) human cases were georeferenced and a set of environmental and climatic variables (wetlands and humid areas, normalized difference vegetation index (NDVI), temperatures and elevation, migratory bird settlements) were used in the analysis. Areas, ecologically similar to those where human cases were detected, were identified using the Mahalanobis distance statistic. A leave‐one‐out cross‐validation was performed to validate the sensitivity of the model, and 78 of 85 points were correctly classified.